Consumers’ psychological constructs regarding hybrid meat products: A scoping review protocol - Jasmijn de Veld; Ceren Pekdemir; Gill ten Hoor (PLoS ONE, 2026)
Objective The objective of this scoping review protocol is to outline the approach for mapping existing evidence on consumers’ psychological constructs and outcomes related to hybrid meat products. Introduction Rising global meat consumption exacerbates environmental and health challenges, while many consumers struggle to reduce their intake through plant-based alternatives alone. Hybrid meat products, combining plant-based and animal-derived components, offer a promising transition pathway toward more sustainable protein consumption. Although research on consumers’ psychological constructs and outcomes to hybrid meat products is growing, a comprehensive overview is lacking. Inclusion criteria The review will use the Population, Concept, Context (PCC) framework, focusing on consumers of any demographic who engage with hybrid meat products. It will include studies that examine at least one psychological construct (e.g., attitude) or outcome (e.g., acceptance) across various settings. Studies conducted in relevant contexts, such as retail environments, restaurants, or experimental settings, will be eligible for inclusion. Methods The review will follow the Joanna Briggs Institute (JBI) methodology and will be reported in accordance with PRISMA-ScR guidelines. A structured search of all relevant publications up to December 2025 will be carried out across multiple databases via EBSCOhost and PubMed. Eligible peer-reviewed English and Dutch articles will be selected based on predefined inclusion criteria. Titles, abstracts, and full texts will be screened sequentially, with reasons for exclusion recorded. Data will be extracted using a tailored extraction tool, with all modifications documented in the final review. The analysis will comprise frequency counts and a descriptive summary of key characteristics and themes, presented in tabular form.